Cuaderno de talleres psicoterapéuticos para la reconstrucción emocional - Díaz Puello, Levis Manuel (Universidad Católica Luis Amigó, 2021)
The Notebook of psychotherapeutic workshops for emotional reconstruction is a therapeutic proposal of individual and/or group intervention to heal the source of emotional pain and stagnation in the lives of children, adolescents, and their families in the hands of professionals with a vocation of service and helping relationship: psychologists, psychiatrists, social workers, religious, therapists, educational psychologists, and nurses. Through different individual sessions, therapeutic cycles, and mixed groups, the intervention has been perfected, including new techniques and psychotherapy methods. Thus, the psychotherapeutic workshops proposed here result from years of clinical practice in attentive and loving listening to the cries for help and despair of the consultants, who reveal their sorrows through their sad looks and their weathered faces from pain and suffering. This work is a gift for all those who decided to accompany others on the path of life.